Plotting for peace : American peacemakers, British codebreakers, and Britain at war, 1914-1917 - Larsen, Daniel, 1985- (Cambridge : Cambridge University Press, 2021)
With Britain by late 1916 facing the prospect of an economic crisis and increasingly dependent on the US, rival factions in Asquith's government battled over whether or not to seek a negotiated end to the First World War. In this riveting new account, Daniel Larsen tells the full story for the first time of how Asquith and his supporters secretly sought to end the war. He shows how they supported President Woodrow Wilson's efforts to convene a peace conference and how British intelligence, clandestinely breaking American codes, aimed to sabotage these peace efforts and aided Asquith's rivals. With Britain reading and decrypting all US diplomatic telegrams between Europe and Washington, these decrypts were used in a battle between the Treasury, which was terrified of looming financial catastrophe, and Lloyd George and the generals. This book's findings transform our understanding of British strategy and international diplomacy during the war.
The First Year Of War (August 1914-August 1915) -- Strategy (August-December 1915) -- Negotiations (January-March 1916) -- Deliberations (March-May 1916) -- The Gamble (June-August 1916) -- The Knock-out Blow (September-October 1916) -- The Fall Of Asquith (October-December 1916) -- Peace Moves (December 1916-January 1917) -- The Zimmermann Telegram And Wilson's Move To War -- (February-April 1917).
Title from publisher's bibliographic system (viewed on 26 Mar 2021).
Keywords: World War, 1914-1918 -- Peace; World War, 1914-1918 -- Cryptography; World War, 1914-1918 -- Economic aspects -- Great Britain; World War, 1914-1918 -- Diplomatic history; United States -- Foreign relations -- Great Britain; Great Britain -- Foreign relations -- 1910-1936.; United States -- Foreign relations -- 1913-1921.; Great Britain -- Foreign relations -- United States